2005
DOI: 10.1207/s1532706xid0501_1
|View full text |Cite
|
Sign up to set email alerts
|

Identity Processes in Adulthood: Diverging Domains

Abstract: Patterns of identity formation were analyzed in a longitudinal framework, from ages 27 to 36 and then to 42 years of age. Information from all 3 ages was available for 197 participants (100 women, 97 men). A variation of Marcia's (1966) Identity Status Interview included 5 domains: religious beliefs, political identity, occupational career, intimate relationships, and lifestyle. Great variability in identity status assessments was found across the domains at each age level. The domains representing work and fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
72
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(80 citation statements)
references
References 30 publications
7
72
0
1
Order By: Relevance
“…In adulthood, Fadjukoff et al (2005) found progressive, regressive and stable trajectories of identity development in both general identity and in various identity domains. Bosma and Gerlsma (2003) give an overview of the trajectories that are theoretically assumed and empirically found.…”
Section: Trajectories Of Identity Developmentmentioning
confidence: 97%
“…In adulthood, Fadjukoff et al (2005) found progressive, regressive and stable trajectories of identity development in both general identity and in various identity domains. Bosma and Gerlsma (2003) give an overview of the trajectories that are theoretically assumed and empirically found.…”
Section: Trajectories Of Identity Developmentmentioning
confidence: 97%
“…Identity commitment has been found to be essential for personal well-being (e.g., Berzonsky, 2003;Fadjukoff & Pulkkinen, 2006;Meeus, Iedema, Helsen, &Vollebergh, 1999;Vleioras & Bosma, 2005). Yet, only about half of young people obtain an achieved identity by early adulthood (Kroger, 2000(Kroger, , 2007, and substantial identity development takes place during adult years for many people (Cramer, 2004;Fadjukoff et al, 2005;Josselson, 1996;Pulkkinen & Kokko, 2000).…”
Section: Changing Economic Conditions and Identity Formation In Adultmentioning
confidence: 99%
“…Secondly, parallel change across the age period and reflections of macro-level economic conditions on reported importance of politics for one's life, sense of control over one's future, and worries about financial problems in the future, as well as on one's own career stability, were investigated, and their association to identity formation was assessed. The role of gender was taken into account in all analyses as domain-specific gender differences have been found in earlier research: In political identity, men are more typically foreclosed and women diffused (Archer, 1989;Fadjukoff, 2007;Fadjukoff et al, 2005;Lewis, 2003;Pastorino & Dunham, 1997) while women generally surpass men in achievement in the interpersonal identity domains (e.g., Fadjukoff et al, , 2005;Lewis, 2003).…”
Section: Changing Economic Conditions and Identity Formation In Adultmentioning
confidence: 99%
“…The interview included five domains through these three age stages: religious beliefs, political ideology, occupational career, intimate relationships, The process of identity formation from age 27 to ages 36 and 42 was described in another context (Fadjukoff, Pulkkinen, & Kokko, 2005). Generally, the data implied an increase of commitment with age: There was an increase in foreclosed identity from age 27 to 36, while identity achievement increased between the ages of 36 and 42.…”
Section: Two Dimensions Of Adaptive Psychological Functioningmentioning
confidence: 99%